Post-error adjustments depend causally on executive attention: Evidence from an intervention study - Li, Qing; Lin, Yixuan; Wang, Xiangpeng; Zhang, Mengke; Stonier, Francis; Chen, Xu; Chen, Antao (Frontiers in Psychology, 2022)
Detecting and correcting execution errors is crucial for safe and efficient goal-directed behavior. Despite intensive investigations on error processing, the cognitive foundations of this process remain unclear. Based on the presumed relation between executive attention (EA) and error processing, we implemented a seven-day EA intervention by adopting the Posner cueing paradigm to test the potential causal link from EA to error processing in healthy adults. The experimental group (high EA, HEA) was trained on the Posner cueing paradigm, with a ratio of invalid cue (IC) trials to valid cue (VC) trials of 5:1 and a corresponding ratio of 1:1 in the active control group (low EA, LEA). We found that the EA intervention improved EA across intervention sessions. Critically, after the EA intervention, the HEA group showed that post-error accuracy (PEA) was restored to the same level as the post-correct accuracy (in comparison with the LEA group). However, post-error slowing and the flanker effect were not modulated by the EA intervention. Furthermore, we observed that the changes in the accuracy of VC trials positively predicted the changes in PEA and that the two groups were classified according to the changes in PEA with a 61.3% accuracy. Based on these results, we propose that EA causally drives error processing. And the capabilities of the “actively catch” more attention resources and the automatic mismatch processing developed after EA intervention is transferable to error processing, thereby directly resulting in the gains in post-error adjustments. Our work informs the potential cognitive mechanisms underlying this causal link.